A novel pseudoautosomal gene encoding a putative GTP-binding protein resides in the vicinity of the Xp/Yp telomere - Gianfrancesco, Fernando; Esposito, Teresa; Montanini, Luisa; Ciccodicola, Alfredo; Mumm, Steven; Mazzarella, Richard; Rao, Ercole; Giglio, Sabrina; Rappold, Gudrun; Forabosco, Antonino (Human molecular genetics, 1998)
We report the cloning of a novel Xp/Yp pseudoautosomal gene called PGPL, and demonstrate that PGPL, like other pseudoautosomal genes, escapes X inactivation and has a functional homologue on the Y chromosome. This gene is expressed in all the tissues examined and is highly conserved across several species. The PGPL gene encodes a protein of 442 amino acids and shows the consensus sequences of a series of motifs of the GTP-binding protein domain. Using fluorescence in situ hybridization analysis on normal males and on patients with rearrangements in the pseudoautosomal region, the gene was localized within 500 kb of the telomere. Further refinement using a cosmid contig of the region places this novel gene within 80-110 kb of the telomere, making this the most telomeric gene on the short arms of the sex chromosomes.
Gesehen am 29.03.2021